Analysis Of Gamification-Based PJOK Learning Implementation To Improve Students' Learning Motivation At State Elementary School 1 Boal, Empang District, Sumbawa Regency - Patrawijaya, Yan; Rahayu, Sri (Lembaga Penelitian dan Pendidikan Mandala, 2026)
This study discusses gamification-based Physical Education, Sports, and Health (PJOK) learning at SD Negeri 1 Boal, Sumbawa Regency. The objectives of this study consist of: 1. To analyze the effectiveness of implementing gamification-based PJOK learning at SD Negeri 1 Boal, Sumbawa Regency. 2. To analyze students' learning motivation in gamification-based PJOK learning at SD Negeri Boal, Sumbawa Regency. 3. To identify supporting and inhibiting factors in implementing gamification-based PJOK learning at SD Negeri 1 Boal, Sumbawa Regency. The study uses a mixed method (Mixed Methods), namely quantitative research with a quasi-experimental design and inferential analysis through independent samples t-test. To compare learning outcomes between the gamification-treated group and the conventional learning group, a qualitative study was conducted with interviews with the principal and physical education teachers. The results showed that gamification-based physical education learning was effective. Statistical findings confirmed a significant difference in student learning outcomes, indicating that the gamification approach significantly impacted student learning motivation. Furthermore, the study identified supporting factors. High student enthusiasm and motivation fueled by the game element; the implementation of gamification elements such as challenges, levels, points, and rewards; adequate facilities and infrastructure; and teacher competence capable of designing and managing gamification effectively. Principal support, teacher creativity, and clear assessment rubrics also strengthen the effectiveness of gamification implementation. However, there are also inhibiting factors such as weather conditions that do not support physical activity, variations in students' physical abilities, forgetting game rules, poor coordination between groups, limited learning time, and limited supporting technology. Overall, this study confirms that gamification is a potential pedagogical approach to strengthen the quality of physical education (PJOK) learning in elementary schools, especially when supported by teacher competence and thorough learning planning.